Progressive multifocal leukoencephalopathy in a patient with chronic lymphocytic leukemia after immunosuppressive treatment. Issue 1 (5th September 2016) - Appel, Shmuel; Nitsan, Zeev; Gelfand, Anna; Tikhmanovich, Natalia; Dorodnicov, Elena; Reznik‐Zoref, Jenia; Milo, Ron; Lugassy, Gilles; Simonovich, Azaria
Abstract: Progressive multifocal leukoencephalopathy is a fatal viral infection of the central nervous system. Magnetic resonance imaging typically shows hyperintense T2/fluid‐attenuated inversion recovery lesions in the periventricular or subcortical white matter without contrast enhancement or gray matter involvement. Herein, we report on a case of a patient with chronic lymphocytic leukemia and developed progressive multifocal leukoencephalopathy with unusual magnetic resonance imaging findings.